Sosialisasi Sadar Wisata dalam Mendorong Partisipasi Masyarakat untuk Pengembangan Pariwisata Berkelanjutan - Roodhi, Mohammad Najib; Dakwah, Muhammad Mujahid; Abdurrahman, Abdurrahman; Muhtarom, Zamroni Alpian; Girsang, Zefanya Andryan; Bratayasa, I Wayan; Switrayana, I Nyoman; Nasri, Muhammad Haris (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2025)
This community service activity was carried out with the main objective of increasing public awareness of the importance of tourism awareness as a foundation for achieving sustainable tourism development, particularly in the coastal area of Batu Layar, Senggigi. The activity was implemented using educational and participatory approaches involving more than 20 community partners, consisting of village officials, youth groups, MSME actors, community leaders, and local representatives. The implementation process included several key stages: delivering awareness material, conducting focused group discussions, simulating tourism service practices, and evaluating participants' understanding through pre-test and post-test assessments. The results of the activity showed a significant improvement in participants' understanding of tourism awareness concepts. This was evidenced by evaluation data, where the average pre-test score of 63.2 increased to 84.5 in the post-test. In addition to the cognitive improvements, this activity also resulted in tangible community impact in the form of collective commitments to support sustainable tourism development. Real actions taken by the community included the formation of a tourism awareness group (Pokdarwis), initiation of beach clean-up programs, and digital tourism promotion through social media platforms. This activity demonstrates that a well-designed, interactive, and stakeholder-inclusive socialization strategy can be an effective means of building collective awareness and encouraging active community participation in developing inclusive, competitive, and sustainable tourism destinations.